2009
DOI: 10.1007/s10295-009-0566-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomass granulation in an aerobic:anaerobic-enhanced biological phosphorus removal process in a sequencing batch reactor with varying pH

Abstract: Long-term influences of different steady-state pH conditions on microbial community composition were determined by fluorescence in situ hybridization (FISH) in a laboratory scale reactor configured for enhanced biological phosphorus removal (EBPR). Chemical profiles were consistent with shifts in populations from polyphosphate-accumulating organisms (PAO) to glycogen-accumulating organisms (GAO) when pH fell from pH 7.5 to 7.0 and then to 6.5. While biomass was both dispersed and flocculated at pH 7.5, almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
(57 reference statements)
2
14
0
1
Order By: Relevance
“…This study contributes to the evidence of sludge granule formation in EBPR processes, which is consistent to reports by other researchers (Ahn et al, 2009;Dulekgurgen et al, 2003;Lin et al, 2003;Wu et al, 2010). Ail of the studies observed sludge granulation in a laboratory-scale SBR seeded with flocculated sludge and fed with synthetic wastewater.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This study contributes to the evidence of sludge granule formation in EBPR processes, which is consistent to reports by other researchers (Ahn et al, 2009;Dulekgurgen et al, 2003;Lin et al, 2003;Wu et al, 2010). Ail of the studies observed sludge granulation in a laboratory-scale SBR seeded with flocculated sludge and fed with synthetic wastewater.…”
Section: Resultssupporting
confidence: 93%
“…Ail of the studies observed sludge granulation in a laboratory-scale SBR seeded with flocculated sludge and fed with synthetic wastewater. The main carbon source in the synthetic wastewater was contributed by acetate in the study conducted by Lin et al (2003), Ahn et al (2009), and in the present work; Dulekgurgen et al (2003) worked solely on acetate-based; and Wu et al (2010) worked solely on propionate-based. The SBR operated in this study was comparable with the one run by Ahn et al (2009) because both SBRs incorporated a six-blade Rushton turbine for mixing purposes.…”
Section: Resultsmentioning
confidence: 83%
“…A significant percentage (up to 16 %) of Tetrasphaera was also detected in a laboratoryscale GSBR fed with acetate, but abundance of this putative PAOs progressively decreased to less than 5 % when propionate was used alone or in mixture with acetate (Weissbrodt et al 2013). Ahn et al (2009) detected Tetrasphaera-related PAOs with Actino-658 probe after starting GSBR only, which was inoculated with activated sludge from full-scale WWTP. Those PAOs were rarely seen in subsequent samples, probably due to inability of Actino-658-targeted Tetrasphaera to utilize acetate.…”
Section: Resultsmentioning
confidence: 97%
“…The settling properties improved, and SVI decreased from 140 ml/g (seeding sludge) to below 30 ml/g on day 171. Ahn et al (2009) showed that dimensions and structure of aerobic granules in a laboratory-scale anaerobic-aerobic GSBR strictly depended on pH value. When pH fell from 7.5 to 6.5, the granules increased in size from 200 to 2000-3000 lm and were regularly spherical with smooth outer surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation